Visibility in Vancouver: screen stories and surveillance of the Downtown Eastside - Walls, Rachel (2011)
This study offers a contribution to the fields of Canadian cultural studies, media studies and surveillance studies, introducing the concept of “screen stories” as a framework for thinking about representations of Vancouver’s contested inner city neighbourhood, the Downtown Eastside, in the contemporary era of heightened visibility as a result of media coverage and widespread state, corporate and self-surveillance. Analysing diverse media forms through the lens of screen stories enables a critique of the complexities of representation and its intersections with surveillance in a neighbourhood that might be regarded as overexposed. Through examination of a unique combination of novels, television drama, documentary and digital media, I show that representation is often complicit in facilitating the scrutiny of the Downtown Eastside and its residents: negative representations are frequently used to justify calls for increased surveillance and security rather than cultivating a better understanding of the neighbourhood. At the same time, I identify strategies of resistance and stories that encourage a multitude of perspectives on the Downtown Eastside, challenging stereotypes and limited assumptions. My development of the concept of “screen stories” emphasises the potential of storytelling through, and about, screen media as a means of balancing or countering surveillant, simulacral or voyeuristic images of the neighbourhood with meaningful, embodied narratives. Situated screen stories provide a means of starting conversations and fostering community, in contrast to the often-divisive effects of surveillance and scrutiny.